Rehabilitation Training Activity Analysis Method for Motor Function in Lower Limb in Elderly Patients with Hemiplegia after Stroke - Meng LYU; Haizhou WANG; Zhuping SHAO (康复学报)
Objective:To observe the effect on rehabilitation training activity analysis for walking ability and motor function in elderly patients with hemiplegia after stroke.Methods:A total of 104 elderly patients with hemiplegia after stroke were randomly divided into control group and observation group, with 52 cases in each group. The control group received routine rehabilitation treatments such as joint balance stabilization training, center-of-gravity transfer training, muscle strengthening training, walking training, and up and down stairs training. The observation group received lower limb rehabilitation training activity analysis based on the control group. We selected some activities related to lower limb movements in the Hong Kong Occupational Therapy Association's daily life activity assessment scale for training. During the training process, we regularly gave a score for each training item. If the score of some training items was equal to or less than 1, we should transform the training environment from activity room to real environment, and carry out intensive training on these items, such as restrict healthy hand to use, strengthen the affected upper limb training, etc.six hours per day, five days per week, continuous treatment for three months. The activity analysis scores, Holden walking function scores, time of walking for 10 m, and Fugl-Meyer motor function scores were compared between two groups.Results:Compared with before treatment, the activity analysis score, Holden walking ability score, and motor function score of the both groups were significantly increased after 1,2 and 3 months after treatment, while the 10 m walking time was significantly reduced, and the differences were statistically significant (P<0.05), Compared with the control group, the activity analysis score, Holden walking ability score, and motor function score of the observation group were higher, and the 10 m walking time was shorter.Conclusion:Rehabilitation training activity analysis method for treatment of elderly patients with hemiplegia after stroke can effectively improve the walking ability, motor function and lower limb physical activity ability of patients with hemiplegia after stroke.